Analisis Pengaruh Jumlah Nilai Taksiran Dan Uang Pinjaman Terhadap Laba Bersih PT. Pegadaian Kanwil XII Surabaya - Hidayati, Syahrotul; Asyhar, Ahmad Hanif; Krisnawan, Alvin (Journal of Mathematics Education and Science, 2025)
PT. Pegadaian is a state-owned company that focuses on secured loans. PT. Pegadaian assesses the property used as collateral before providing a loan. The purpose of this study is to see how the number of appraisals and loan money has an impact on PT. Pegadaian's net profit both partially and simultaneously. This study uses multiple linear regression analysis. The research sample and population were PT. Pegadaian Kanwil XII Surabaya, which reported the appraisal value, loan amount, and net profit during the period 2020-2023. The results showed that the net profit of PT. Pegadaian was not partially influenced by the loan and appraisal variables. This may indicate a correlation that is not strong, a significant variable that is not taken into account, or a non-linear correlation that has not been detected. However, PT. Pegadaian net profit is influenced by both variables simultaneously.